Indonesia SISTEM PENDUKUNG KEPUTUSAN PRIORITAS USULAN SERTIFIKASI TENAGA PENDIDIK DI SMP NEGERI 2 CISOKA DENGAN METODE TOPSIS: Indonesia - Sudesi, Ziki (PT Triputra Sejahtera Prima, 2023)
The government has issued various policies as an effort to improve the quality of learning and education in Indonesia, one of which is teacher certification. The implementation of teacher certification began in 2007 after the issuance of Minister of National Education regulation number 18 of 2007 concerning in-service teacher certification. Government regulation number 74 of 2008 concerning teachers is the basis for implementing teacher certification. However, in determining teacher certification participants, the evaluations carried out were still conventional, therefore the authors took the initiative to design and create a decision support system to determine the priorities of teacher certification participants. The decision support system has several methods that are used, one of which is TOPSIS (Technique Order Preference by Similarity To Ideal Solution). TOPSIS is based on the concept where the best selected alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. . This method is widely used to solve practical decision making. Priority decision making for teacher certification participants uses criteria in their assessment, these criteria are the teacher's tenure, teacher age, teacher class/rank, teacher workload, additional assignments and work performance obtained. The results of the system conclude that this decision support system assist in determining teacher certification participants.